2021
DOI: 10.1186/s41938-021-00462-x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity analysis of antagonistic microbes against bacterial leaf and fungal sheath blight diseases of rice

Abstract: Background Biocontrol is an effective strategy in the integrated management of plant diseases, now more as a necessity than choice, in the present era of environmental and health awareness. Microbial diversity is a wonder by nature that inspires to explore and accordingly, the diversity analysis of the isolated microbes revealed their morphological and molecular differences. The DNA provides a common platform to store the microbial information in the form of databases in public domain that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
2
15
0
1
Order By: Relevance
“…They also produce plant growth-promoting hormones and other alkaloids like siderophores which improves availability of Fe to the plants (Stuti et al, 2021). The other bioagents viz., TAIK1 and BIK3 were found to improve all plant growth parameters in rice as reported earlier (Kannan et al, 2021). Trichoderma help plants to acquire nutrients such as phosphorus, nitrogen, and other micronutrients by secreting enzymes that break down organic matter in the soil and converts complex matter to simpler substances (Yedidia, et al, 2000).…”
Section: Discussionsupporting
confidence: 67%
“…They also produce plant growth-promoting hormones and other alkaloids like siderophores which improves availability of Fe to the plants (Stuti et al, 2021). The other bioagents viz., TAIK1 and BIK3 were found to improve all plant growth parameters in rice as reported earlier (Kannan et al, 2021). Trichoderma help plants to acquire nutrients such as phosphorus, nitrogen, and other micronutrients by secreting enzymes that break down organic matter in the soil and converts complex matter to simpler substances (Yedidia, et al, 2000).…”
Section: Discussionsupporting
confidence: 67%
“…Significant bioactivity of the protein at higher temperatures (45 • C) indicates the thermostability of the protein to withstand application in the late sown crop in tropical conditions, where the temperature ranges above 35 • C during most stages of the crop cycle [31]. Positive compatibility studies of Bg_9562 with native antagonistic/plant growth promoting fungi and bacteria isolated and characterized at this institute, viz., TAIK and BIK3 strains [18], would help in co-application of Bg_9562 along with the biocontrol agents for the management of ShB disease in rice. In addition to their plant protection properties, plant growth promotion by Bacillus and Trichoderma species will give an additional benefit to the plants.…”
Section: Discussionmentioning
confidence: 99%
“…The physicochemical properties, transmembrane regions, and thermal stability-related residues of the protein were determined in silico and correlated with wet-lab experiments and bioactivity assays of Bg_9562 on RS. The interaction of Bg_9562 with potential native biocontrol agents Trichoderma asperellum TAIK1 and Bacillus subtilis BIK3 [18] was studied, which helps in the use of this protein along with the biocontrol agents. In summary, this study aims to identify the antimicrobial properties of Bg_9562 for its effective usage as a biocontrol agent to fight against sheath blight disease of rice.…”
Section: Introductionmentioning
confidence: 99%
“… The table is modified from Tables 1 and 2 from the article referred - 10.1186/s41938-021-00462-x [1] . …”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…For instance, TAIK1 application on 30 th day of transplantation released growth promoting substances and also suppress the infection induced by R. solani and S. oryzae. It has also been reported that the bioagents application needs to be standardised for different varieties [1] .…”
Section: Value Of the Datamentioning
confidence: 99%